IRANIAN UNIVERSITY LEARNERS’ ENGLISH VOCABULARY LEARNING USING SYNONYM AND L1 TRANSLATION - Husain Abdulhay (Journal of Research on Language Education, 2023)
Vocabulary is part and parcel of learning of a second or a foreign language. This study examined the effect of vocabulary learning through translation of English words (Persian equivalents) and the use of English synonym on the retention and retrieval of vocabularies. Static-group comparison design was utilized to scrutinize sixty EFL learners split into two groups. The experimental group was instructed on the memorizing strategies and the control one left alone to memorize words presented in class in a week time span. The experimental group being taught on coding, interim device, and visual imagery strategies was assayed on spot by dint of written word recognition tests for their receptive knowledge of synonyms written on the board. The findings of the matching test tasks divulged that the learners’ recognitions of synonyms than the first language equivalents were significantly higher. The experimental group significantly scored higher in the recognition test of synonyms than that of translation equivalents. Results have practical implications and application for foreign language learning and teaching which are discussed.